The role of sensory processing difficulties, cognitive impairment, and disease severity in predicting functional behavior among patients with multiple sclerosis. Issue 8 (10th April 2021) - Engel-Yeger, Batya; DeLuca, John; Hake, Patrick; Goverover, Yael
Abstract: Purpose: To compare sensory processing and functional behavior abilities between participants with multiple sclerosis (MS), with and without cognitive impairments, and healthy controls, and to examine the role disease severity, cognitive impairment, and sensory processing have in predicting the functional behavior of persons with MS. Methods: Sixty-one participants with MS were enrolled in this study, 43 with cognitive impairments and 18 without (based on the Brief International Cognitive Assessment for MS composite z -score), and 36 healthy controls. Participants were between the ages 23 and 63 and asked to complete the Adolescent/Adult Sensory Profile, Functional Behavior Profile, and MS Functional Composite. Results: Both MS groups showed sensory processing difficulties with lower ability to register sensory input and greater sensory sensitivity and avoidance versus healthy controls. Among both MS groups, sensory processing difficulties correlated with greater disease severity and poor functional behavior in daily life. The significant predictors of functional behavior in daily life were a lower ability to register sensory input and greater sensory avoidance. Conclusions: Persons with MS have sensory processing difficulties regardless of their cognitive abilities, which negatively affect their functional behavior. Research and practice should further explore the role of sensory processing as expressed in daily scenarios for persons with MS and consider the functional impacts of this study in order to optimize daily life experiences for patients. Implications for rehabilitation: Sensory processing difficulties in multiple sclerosis (MS) are mainly expressed in poor ability to register and modulate sensory input from daily environment, regardless of patients' cognitive status. Sensory processing difficulties in MS may affect patients' ability to perform activities of daily living. Sensory processing difficulties in MS should be evaluated using objective measures (electrophysiology tools) as well as self-reports that reflect patients' difficulties in real life context. Intervention programs in MS should refer to sensory processing difficulties, to their correlation with disease severity, cognitive status and to their impacts on people's daily function.